Referencing web pages and e-journals. (December 2013) - Bryson, David
<x xml:space="preserve">Abstract</x> One of the areas that can confuse students and authors alike is how to reference web pages and electronic journals (e-journals). The aim of this professional development article is to go back to first principles for referencing and see how with examples these should be referenced.